2022
DOI: 10.1101/2022.10.25.513668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HSPB1 facilitates chemoresistance through inhibiting ferroptotic cancer cell death and regulating NF-κB signaling pathway in breast cancer

Abstract: Chemoresistance is one of the major causes of therapeutic failure and poor prognosis for breast cancer patients, especially for triple-negative breast cancer patients. However, the underlying mechanism remains elusive. Here, we identified novel functional roles of heat shock protein beta-1 (HSPB1), regulating the chemoresistance and ferroptotic cell death in breast cancer. Based on TCGA and GEO databases, HSPB1 expression was upregulated in breast cancer tissues and associated with poor prognosis of breast can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Studies have suggested that high HSPB1 expression predicts poor clinical outcomes in several cancers, including breast cancer, hepatocellular carcinoma, gastric cancer, lung cancer, and pancreatic cancer. [32][33][34][35][36] We also discovered that the expression of HSPB1 was elevated in a variety of cancers, including GBM. Consistent with previous reports, we found that patients with GBM who had elevated expression of HSPB1 had shorter OS, DSS, and PFI than those with lower HSPB1 expression.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have suggested that high HSPB1 expression predicts poor clinical outcomes in several cancers, including breast cancer, hepatocellular carcinoma, gastric cancer, lung cancer, and pancreatic cancer. [32][33][34][35][36] We also discovered that the expression of HSPB1 was elevated in a variety of cancers, including GBM. Consistent with previous reports, we found that patients with GBM who had elevated expression of HSPB1 had shorter OS, DSS, and PFI than those with lower HSPB1 expression.…”
Section: Discussionmentioning
confidence: 98%
“…However, the role of STUB1 in regulating ferroptosis through ubiquitination in the development of lung cancer is still relatively rare. Recent studies have shown that HSPB1 functions as a ferroptosis suppressor in the context of ferroptosis, 26 where it promotes chemoresistance in breast cancer cells by inhibiting ferroptosis and modulating the NF‐κB signaling pathway 27 . Targeting HSPB1 for the regulation of ferroptosis also mitigates sorafenib resistance in hepatocellular carcinoma 24 .…”
Section: Introductionmentioning
confidence: 99%